Interaction Law between Natural Fractures-Vugs and Acid-Etched Fracture during Steering Acid Fracturing in Carbonate Reservoirs - Yifan Dai; Bing Hou; Changlin Zhou; Kunpeng Zhang; Fei Liu (Geofluids)
Steering acid fracturing is a technique that improves the conductivity of carbonate reservoir. It is widely used in a carbonate reservoir. However, due to the lack of comparative experiments, the application of steering acid to improve the fracturing results is still unknown. Therefore, a series of true triaxial acid fracturing experiments were conducted to study steering acid fracturing in carbonate reservoir. The carbonate specimens used in the experiment were from the Qixia group and Dengsi Member in Sichuan, China. In this study, slick water, cross-linked gel, and self-generating acid were used as ahead fluid to cooperate with steering acid. Experimental results show that (1) the low-viscosity ahead fluid with steering acid can result in more complex fractures; (2) the complexity of fractures is influenced by natural fracture and the viscosity of the ahead fluid; and (3) based on the 3D scanning results of the fracture surface, different ahead fluids will lead to different corrosion results. This study provides useful suggestions on steering acid fracturing design and physical simulation experiments.